Discs large 5, an Essential Gene in Drosophila, Regulates Egg Chamber Organization. Issue 5 (1st May 2015) - Reilly, Eve; Changela, Neha; Naryshkina, Tatyana; Deshpande, Girish; Steward, Ruth
Abstract: Discs large 5 (Dlg5) is a member of the MAGUK family of proteins that typically serve as molecular scaffolds and mediate signaling complex formation and localization. In vertebrates, Dlg5 has been shown to be responsible for polarization of neural progenitors and to associate with Rab11-positive vesicles in epithelial cells. In Drosophila, however, the function of Dlg5 is not well-documented. We have identified dlg5 as an essential gene that shows embryonic lethality. dlg5 embryos display partial loss of primordial germ cells (PGCs) during gonad coalescence between stages 12 and 15 of embryogenesis. Loss of Dlg5 in germline and somatic stem cells in the ovary results in the depletion of both cell lineages. Reduced expression of Dlg5 in the follicle cells of the ovary leads to a number of distinct phenotypes, including defects in egg chamber budding, stalk cell overgrowth, and ectopic polar cell induction. Interestingly, loss of Dlg5 in follicle cells results in abnormal distribution of a critical component of cell adhesion, E-cadherin, shown to be essential for proper organization of egg chambers.